DEFAMILIARIZATION OF CHARACTER IN ANTOINE DE SAINT EXUPERY’S THE LITTLE PRINCE - Nora Dita Zakiah; Tri Premesti (Universitas 17 Agustus 1945 Surabaya, 2019)
Defamiliarization is a device of art to make things unfamiliar by a process of making strange (estrangement) to increase the difficulty and length the perceptions. The Little Prince, a novella by Antoine De Saint Exupery presents the defamiliarized characters which appear strange and unfamiliar. To recognize them, the character’s familiarity should be identified by the schemata study before came into defamilarization. Experiencing the artfulness of object will give the reader chance to discover any kind of perceived meaning without inhibition for their judgments. This study uses qualitative method in terms of close reading technique in scrutinizing Antoine de Saint Exupery’s The Little Prince. The discussion is conducted through its characters. Although those device are common objects, they appeared strange to open the reader’s mind into any possible assumptions, meaning, and interpretation.